Biocidal Activities of Some 2-Amino Biphenyl Derived Amides - KUMAR PATHAK, PAWAN; KUSHWAHA, B.S.; KUMAR RATHORE, DEEPAK (Asian Journal of Chemistry, 2010)
Several 2-amino biphenyl derived amides have been found active against various microogranisms. 2-Amino biphenyl itself active against various infectious and dreadful microorganisms. Biologically active 2-amino biphenyl derived amides have been obtained from the condensation of 2-amino biphenyl and different acid chlorides.